2016
DOI: 10.1155/2016/6215745
|View full text |Cite
|
Sign up to set email alerts
|

Eclectic Ocular Comorbidities and Systemic Diseases with Eye Involvement: A Review

Abstract: Coexistence of several ocular diseases is more frequent than suspected. In spite of the refractive errors, one or more of the following can be detected simultaneously: glaucoma, cataracts, uveitis, age-related macular degeneration, and dry eyes. In addition, as people age, ocular comorbidities are much more usually seen. Specific diseases are openly acknowledged to affect the eyes and vision, such as diabetes mellitus, hypertension blood pressure, arthritis, hyperthyroidism, neurodegenerative disorders, hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 77 publications
2
38
0
Order By: Relevance
“…The most frequent disease association (encountered in 9,087 male patients irrespective of direction) was found to be between chronic bronchitis (ICD-9 code 491) and other diseases of lung (518), the latter encompassing various diseases, such as, pulmonary collapse , interstitial emphysema , acute edema of lung , etc. 16 . Other significant comorbidities include pairs of different respiratory diseases (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent disease association (encountered in 9,087 male patients irrespective of direction) was found to be between chronic bronchitis (ICD-9 code 491) and other diseases of lung (518), the latter encompassing various diseases, such as, pulmonary collapse , interstitial emphysema , acute edema of lung , etc. 16 . Other significant comorbidities include pairs of different respiratory diseases (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A significant number of comorbidities (40%) within the thirty most populated disease associations reported in Table 1 for the male sub-population, involve cataract (366), such as, cataract with respiratory and cardiovascular diseases, as well as, with osteoarthrosis (715), hyperplasia of the prostate (600), bladder cancer (188) and diabetes mellitus (250), all disorders known to affect the eye, among others 16 . Diabetes is known to be an important risk factor for the formation of cataract and epidemiologic studies have demonstrated that cataracts are the most common cause of visual impairment in older-onset diabetic patients 17 , 18 .…”
Section: Resultsmentioning
confidence: 99%
“…To date, only a few studies have mentioned the issue of an association between glaucoma and retinal diseases. 19,20 One prior study which included 5154 patients with glaucoma in the United States showed that glaucoma is frequently accompanied by retinal comorbidities. 20 In addition, patients with primary OAG (15.7%) had 20 However, no previous literature has investigated the association between OAG and neovascular AMD to date, although these two diseases may share similar pathophysiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The retina and optic nerve form part of the central nervous system and are derived from the diencephalon during early foetal development [3]. In many diseases, including diabetes mellitus, hypertension, and arthritis, characteristic signs develop in the retina [4]. This study investigated whether changes reported in the retinas of typically developing patients with mild cognitive impairment (MCI) or dementia are also observed in the retinas of adults with DS, before clinical evidence of dementia.…”
Section: Introductionmentioning
confidence: 99%